The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1111/mpp.12211
|View full text |Cite
|
Sign up to set email alerts
|

Oxaloacetate acetylhydrolase gene mutants of Sclerotinia sclerotiorum do not accumulate oxalic acid, but do produce limited lesions on host plants

Abstract: The oxaloacetate acetylhydrolase (OAH, EC 3.7.1.1)-encoding gene Ss-oah1 was cloned and functionally characterized from Sclerotinia sclerotiorum. Ss-oah1 transcript accumulation mirrored oxalic acid (OA) accumulation with neutral pH induction dependent on the pH-responsive transcriptional regulator Ss-Pac1. Unlike previously characterized ultraviolet (UV)-induced oxalate-deficient mutants ('A' mutants) which retain the capacity to accumulate OA, gene deletion Δss-oah1 mutants did not accumulate OA in culture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
154
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(158 citation statements)
references
References 53 publications
3
154
1
Order By: Relevance
“…OA can be synthesized from a variety of precursors, but in fungi the most common mechanism is through the hydrolysis of oxaloacetate to form OA and carbon dioxide. An oxaloacetate acetyl hydrolase (OAH) has been characterized in S. sclerotiorum [114] and disruption of the OAH gene in Aspergillus niger , B. cinerea [115] and S. sclerotiorum leads to loss of oxalic acid production and reduced virulence [116]. In the current study, the S. sclerotiorum OAH gene (SS1G_08218) was expressed from 1 hpi, but only up-regulated at 48 hpi with 5- fold greater levels than the inoculum.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…OA can be synthesized from a variety of precursors, but in fungi the most common mechanism is through the hydrolysis of oxaloacetate to form OA and carbon dioxide. An oxaloacetate acetyl hydrolase (OAH) has been characterized in S. sclerotiorum [114] and disruption of the OAH gene in Aspergillus niger , B. cinerea [115] and S. sclerotiorum leads to loss of oxalic acid production and reduced virulence [116]. In the current study, the S. sclerotiorum OAH gene (SS1G_08218) was expressed from 1 hpi, but only up-regulated at 48 hpi with 5- fold greater levels than the inoculum.…”
Section: Resultsmentioning
confidence: 71%
“…Release of OA causes a reduction in ambient pH, which stimulates hydrolytic enzyme production throughout the course of the infection [112, 118], as well as sclerotogenesis during its final stages [7, 119], though OA may not be the sole determinant affecting tissue acidification [120]. Interestingly, fine-tuning of OA levels through the activity of OA biogenic [121] and degradative [116] enzymes appears to be critical for early host-pathogen interactions as well, including compound appressorium formation and lesion expansion.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, this study has shown that S. sclerotiorum infects its host in two phases: phase I – primary lesion formation where OA accumulation is low and may not be significant, and phase II – colonization where OA is required. The low OA levels observed during primary lesion formation in OxO‐OE has also been noted by Heller & Witt‐Geiges () and is in agreement with the observation that primary lesions can form in the presence of OA‐reduced mutants (Cessna et al ., ; Kim et al ., ; Williams et al ., ) and OA‐minus mutants that produce no OA (Liang et al ., ; Xu et al ., ). It is becoming apparent to the authors, and others, (Kabbage et al ., ; Liang et al ., ; Xu et al ., ), that factors other than OA have major roles during primary lesion formation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Liang et al . () and Xu et al . () have shown, independently, that S. sclerotiorum knockout mutants that generate no OA can establish primary lesions but have limited ability to colonize the host.…”
Section: Introductionmentioning
confidence: 90%
“…S. sclerotiorum colonization is associated with many enzymes that are capable of digesting and degrading the cell wall of the host. In addition, several authors have associated the production of oxalic acid (OA) with virulence (HAREL et al, 2006;KIM et al, 2008;WALZ et al, 2008;LIANG et al, 2015). Therefore, some susceptibility screening assays are based on the responses of different genotypes to oxalic acid (GONÇALVES;SANTOS, 2010), however, the authors are not aware of any publications assessing the levels of resistance of soybean to S. sclerotiorum based on the wilting responses of OA, as has been efficiently used for common bean (KOLKMAN; KELLLY, 2000;ANTONIO et al, 2008).…”
Section: Introductionmentioning
confidence: 99%